To Study the Impact of Just-In-Time System - Jessica , Yap; Sorooshian, Shahryar (Journal of Management and Science, 2013)
The purpose of this research is to study the Impact of Just-In-Time (JIT) system on inventory and financial performance. JIT production has received a great deal of attention, worldwide, since its introduction in Japan a few decades ago. It has been well documented that some of the main benefits of JIT implementation are reduction of inventories and cost savings. JIT philosophy has been primarily used in manufacturing operations to manage materials and other production activities. The overall goal of JIT is to eliminate waste and it is a continuous process that can be viewed in terms of the extent to which the culture and philosophy of JIT permeates the organization.